The cinematic hidden Christ – His invisible divinity and his visible humanity - Brinkman, Martien E (Stellenbosch Theological Journal, 2017)
If we want to reflect upon the impact of the many ‘hidden Christ’-images in modern films at a theologically responsible way, we need to incorporate that reflection into our doctrine of revelation. That will imply that we have to re-open the classical Gospel-Culture discussion. Especially in the United States we can recognize a lot of original approaches to this issue in Reformed circles (Wolterstorff, Dyrness, Begbie, Seidell, etc.). The main question to be put in this article will be: How can we develop criteria to assess the depiction of the divine in these films?